Orientation of germanium nanowires on germanium and silicon substrates for nanodevices. (2020) - Beretta, S.; Bosi, M.; Seravalli, L.; Musayeva, N.; Ferrari, C.
Abstract: Germanium nanowires were grown using gold colloids on germanium and silicon substrates, (0 0 1) and (1 1 1) oriented. The presence of Si oxide on the surface inhibits the epitaxial growth of the nanowires, resulting in the presence of randomly oriented nanostructures. Different etching procedures of Si oxide are discussed and evaluated, with the goal to obtain epitaxial nanowires aligned with the substrate crystallographic directions. Germanium oxide may be thermally etched during the growth procedure, so that on Ge substrates the nanowires are generally well aligned without any wet-etch. We also study the effect of sonication of the nanowires, to minimize the damage to the nanostructures when they are dropcasted to a carrier substrate for further studies.